2022
DOI: 10.3389/fendo.2022.982493
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and infant outcomes in women with and without gestational diabetes mellitus in the COVID-19 era in China: Lessons learned

Abstract: AimsThe global COVID-19 pandemic has required a drastic transformation of prenatal care services. Whether the reformulation of the antenatal care systems affects maternal and infant outcomes remains unknown. Particularly, women with gestational diabetes mellitus (GDM) are among those who bear the greatest brunt. Thus, this study aimed to evaluate the impact of COVID-19 lockdown during late pregnancy on maternal and infant outcomes in women stratified by the GDM status in China.Study designThe participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Levels of fasting plasma glucose were higher in women with GDM and SARS-CoV-2 infection compared with those with GDM before the pandemic; the majority of the infected women were symptomatic with COVID-19-related symptoms. Similar results were recently published by others 31. In our study, for most women the SARS-CoV-2 infection was diagnosed with or shortly after GDM was confirmed.…”
Section: Discussionsupporting
confidence: 93%
“…Levels of fasting plasma glucose were higher in women with GDM and SARS-CoV-2 infection compared with those with GDM before the pandemic; the majority of the infected women were symptomatic with COVID-19-related symptoms. Similar results were recently published by others 31. In our study, for most women the SARS-CoV-2 infection was diagnosed with or shortly after GDM was confirmed.…”
Section: Discussionsupporting
confidence: 93%
“…[34][35][36] Diabetes has been linked to worse outcomes in COVID-19 patients in other studies. [37][38][39] This includes not only a higher risk of severe illness, but also complications from COVID-19. 40 examined with multivariate analysis, which revealed that diabetics with COVID-19 had a higher risk of death, ICU admission, and prolonged hospital stays.…”
Section: Discussionmentioning
confidence: 99%
“…In the wake of the COVID‐19 pandemic, Mexico has seen an increase in the number of diabetes cases 34‐36 . Diabetes has been linked to worse outcomes in COVID‐19 patients in other studies 37‐39 . This includes not only a higher risk of severe illness, but also complications from COVID‐19 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible increase in the prevalence of GDM during the pandemic may be due to several reasons, such as behavioral changes during lockdown, direct damage to pancreatic beta cells by the virus, or an infection-induced increase in insulin resistance. The following results can be derived from numerous studies on this question: ▪ GDM prevalence is increasing possibly associated with changes in screening procedures or lifestyle changes [57][58][59][60][61][62]; ▪ GDM prevalence does not change or is decreasing [63][64][65][66]; ▪ GDM is associated with a severe course of COVID-19 or insulin therapy [23,67]; ▪ Gestational weight gain (GWG) as a risk factor for GDM increases [68]. Taken together, from the existing literature there is some evidence that during the first two years of the pandemic and with low vaccination rate GDM prevalence increased locally, probably secondary to changes in lifestyle, such as less exercise, increasing BMI during lockdown, and GWG.…”
Section: Gdm Prevalence and Outcomes During The Pandemicmentioning
confidence: 99%